No Explanation Required a woman's guide to assert your confidence and master communication at work - Sankar, Carol (McGraw Hill Education, 2022)
"Real-world communication strategies to help you break into the C-suite-and thrive when you arrive! With only 5.8% of CEO positions in the S&P 500 held by women, it's clear that there are more women who deserve a seat at the table than actually have one. In No Explanation Required!, Carol Sankar gives you the strategies you need to create the success you deserve-today. As founder of the global leadership firm, The Confidence Factor for Women, her goal is to ensure you deliver decisions and other communications with confidence-no "explanations" required! Loaded with real-life examples and backed by proprietary research, No Explanation Required! coaches you on how to speak up for yourself, stop debating your decisions, and eliminate "limiting" language. In example after example, it becomes clear how these too-frequent expressions ("I'm sorry," "Excuse me," "I'll get back to you") can strip you of your authority and credibility. With the tactics in No Explanation Required mastered, you'll be better equipped to stop explaining and start negotiating-for gender parity, better compensation, opportunities, and more"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Business communication; Women -- Communication; Self-esteem in women; Confidence; Communication dans l'entreprise; Femmes; Communication; Estime de soi chez la femme; Confiance; Women; Communication